Landfill Mining: Development of a cost simulation model - Wolfsberger, Tanja; Pinkel, Michael; Polansek, Stephanie; Sarc, Renato; Hermann, Robert; Pomberger, Roland (Waste management & research, 2016)
Landfill mining permits recovering secondary raw materials from landfills. Whether this purpose is economically feasible, however, is a matter of various aspects. One is the amount of recoverable secondary raw material (like metals) that can be exploited with a profit. Other influences are the costs for excavation, for processing the waste at the landfill site and for paying charges on the secondary disposal of waste. Depending on the objectives of a landfill mining project (like the recovery of a ferrous and/or a calorific fraction) these expenses and revenues are difficult to assess in advance. This situation complicates any previous assessment of the economic feasibility and is the reason why many landfills that might be suitable for landfill mining are continuingly operated as active landfills, generating aftercare costs and leaving potential hazards to later generations. This article presents a newly developed simulation model for landfill mining projects. It permits identifying the quantities and qualities of output flows that can be recovered by mining and by mobile on-site processing of the waste based on treatment equipment selected by the landfill operator. Thus, charges for disposal and expected revenues from secondary raw materials can be assessed. Furthermore, investment, personnel, operation, servicing and insurance costs are assessed and displayed, based on the selected mobile processing procedure and its throughput, among other things. For clarity, the simulation model is described in this article using the example of a real Austrian sanitary landfill.